Clinical Attributes and Electroencephalogram Analysis of Patients With Varying Alpers’ Syndrome Genotypes - Li, Hua; Wang, Wei; Han, Xiaodi; Zhang, Yujia; Dai, Lifang; Xu, Manting; Deng, Jie; Ding, Changhong; Wang, Xiaohui; Chen, Chunhong; Yang, Xiaofeng; Fang, Fang (Frontiers in Pharmacology, 2021)
Alpers, syndrome is an early-onset neurodegenerative disorder with a poor prognosis, characterized by the triad of developmental regression, intractable epilepsy, and hepatic dysfunction With increased access to whole exome sequencing (WES), new candidate genes are being identified although there are fewer large cohort papers describing the clinical phenotype in such patients. To better characterize the phenotypic, genetic, and electroencephalographic features of children with Alpers’ syndrome. Here, we investigated 7 patients with Alpers’ Syndrome, who received treatment in Beijing Children's Hospital and had detailed clinical, electroencephalogram (EEG), and genetic information. Conversely, we performed an extensive literature search in PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Chinese BioMedical Literature Database, China National Knowledge Infrastructure Database, using the term “Alpers’ Syndrome”and“EEG” and were able to ﬁnd 19 cases reported from January 2008 to May 2020. Our study find the patients carrying different pathogenic variants exhibited similar phenotypes. RHADS are a highly specifific EEG phenomenon for diagnosis of Alpers’ syndrome and can be reliably recognized during the active phase of the syndrome. Clinical expression and EEG ripples suggest that they signify an epileptic phenomenon.